Performance Improvement of Organic Light Emitting Diodes Using Poly(N-vinylcarbazole) (PVK) as a Blocking Layer - Lee, Joo-Woon; Kim, Jai-Kyeong; Yoon, Young-Soo (WILEY-V C H VERLAG GMBH, 2010)
High efficiency organic light-emitting-devices (OLED) have been fabricated by incorporation of a polymeric layer as a controller of the Unbalanced charge. In device configuration of ITO/PEDOT:PSS/PVK/Alq(3)/LiF:Al, poly(N-vinylcarbazole) (PVK) was selected as a blocking layer (BL) because it has a hole transporting property and a higher band gap, especially a lower LUMO level than the emitting layer (Alq(3)) and a higher HOMO level than the hole injection layer (PEDOT: PSS). As a result, the optimal structure with this bl layer showed a peak efficiency of 6.89 cd/A and 2.30 lm/W compared to the device without the PVK layer of 1.08 cd/A, 0.27 lm/W. This result Shows that the PVK layer could effectively block the electrons from metal cathode and confine them in the emitting layer and accomplish the charge balance, which leads to enhanced hole-electron balance for achieving high recombination efficiency.
Keywords: ELECTROLUMINESCENT DEVICES; ELECTRON INJECTION; EFFICIENCY